EVALUASI PELAKSANAAN E-LEARNING PADA SISWA KELAS XI SMK PERMATA HARAPAN - Ilmi, Miftahul (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2021)
This study aims to evaluate the use of e-learning at Permata Harapan Vocational School in terms of context, input, process and results obtained from the application of the use of e-learning. The research model used is CIPP with a mix-method method that combines two methods into one, namely quantitative and qualitative methods in a row so that the results of this research can be better and can be interpreted well. Research at Permata Harapan Vocational School shows the results based on an evaluation using the CIPP evaluation method on 36 class XI students of Permata Harapan Vocational School which are included in the good category and reach a percentage of 85.90%, where the details of each aspect can be seen as follows: starting from the context aspect with an achievement of 85.76%, input aspects 88.24%, process aspects 84.32% and product aspects 85.32% where these results are deepened by the results of qualitative research that are in line. This proves that the use of e-learning at Permata Harapan Vocational School is quite good, although there are still some things that must be added to get better results in the future. Keywords: Evaluation, CIPP, Vocational School, mix method.